The prediction of Quality of Life Dimensions on Stress coping Strategies in patients with Cancer - Negin Maleknia; Farhad Kahrazei (Mashhad University of Medical Sciences, 2015)
Background & aim: The purpose of the present study was to determine the relationship between stress coping styles and quality of life (QOL) among patients with breast cancer. Methods:This descriptive correlational study was conducted on 50 patients with breast cancer, selected via convenience sampling in Kerman, Iran. To collect data Stress Coping Strategy Scale (Moss and Billings, 1982) and the EORTC Quality of Life Questionnaire (QLQ-C30, version 3.0) were used. For data analysis, Pearson's correlation coefficient and stepwise regression analysis were conducted using SPSS version 21. Results: The results showed a significant positive relationship between problem-focused coping strategies and two dimensions of QOL including total symptoms and functional scale (P=0.01). In addition, emotion-focused coping strategies had a significant negative correlation with total symptoms and functional dimension of QOL (P=0.01). Emotion-focused coping styles predicted a higher rate of the variance in the functional dimension of QOL compared to problem-focused coping styles (34.7% vs. 26.2%). The functional scale was significantly correlated with problem-focused coping styles (P=0.001 and β= 0.512), indicating the predictive value of this scale. Moreover, the functional dimension of QOL was significantly correlated with emotion-focused coping strategies (P=0.001 and β=-0.612), showing the significance of this scale as a negative predictor. Conclusion: Problem-focused coping styles had the most significant contribution to the functional scale of QOL. Thus it can be concluded that usig problem-focused coping styles can be effective for adjusting the psychological reactions of patients and coping with the disease in the breast cancer patients.